Prominent Secondary Metabolites from Selected Genus of Avicennia Leaves - Basyuni, Mohammad (Open Access Maced J Med Sci, 2019)
BACKGROUND: Mangrove plants distributed in the intertidal of the tropical and subtropical region including in North Sumatra, Indonesia. The production of secondary metabolite compounds is well known to mangroves. Characterisation of prominent compounds from mangrove plants such as genus of Avicennia is required to explore for their biological and pharmacological properties of these compounds. AIM: The purpose of this research was to analyse the prominent secondary metabolites through the characterisation of phytochemical, physicochemical, and microscopic of the mangrove genus Avicennia leaves, particularly Avicennia alba, A. lanata, A. marina, and A. officinalis. METHODS: Phytochemical screening was carried out on Avicennia spp leaves to the established process. Physicochemical characters of mangrove leaves were investigated by simplicial powder consisting of moisture content, water-soluble, ethanol-soluble, ash content and ash soluble acid according to the WHO formula. Microscopic analysis on the simplicial powder was carried out based on the WHO procedure. RESULTS: The result showed that physicochemical feature displays diversity among the species and important findings on the water concentration was less than 10% as a prerequisite for the drug. The phytochemical search of simplified grain also depicted divergence among the species, only alkaloid, saponin, and triterpenoid or phytosterol were found entirely in Avicennia spp leaves. Microscopic search found a similar type of stoma in Avicennia spp leaves, namely diacytic. CONCLUSION: The prominent secondary metabolites in Avicennia spp leaves consisting of alkaloid and saponin in simplicial and triterpenoid/sterol was either in simplicial or hexane extract. The present study may provide significant pharmacological properties from mangrove Avicennia genus green foliages, which could accelerate another prospect for non-wood mangrove utilisation.